2020
DOI: 10.1038/s41598-020-69327-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel multiparameter correlates of Coxiella burnetii infection and vaccination identified by longitudinal deep immune profiling

Abstract: Q-fever is a flu-like illness caused by Coxiella burnetii ( Cb ), a highly infectious intracellular bacterium. There is an unmet need for a safe and effective vaccine for Q-fever. Correlates of immune protection to Cb infection are limited. We proposed that analysis by longitudinal high dimensional immune (HDI) profiling using mass cytometry combined with other measures of vaccination and protection could be used to identify novel correlates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…Both CpG and QuilA were found to be strong Th1 polarizing adjuvants, as indicated by the IgG2c skewed response, which has been suggested to be an important correlate of protective immunity against Q fever. 15,50,56 Further analysis of serological responses to Sol II revealed a dose-dependent correlation with an increasing IgG2c ratio. Increasing the number of doses or administering a higher dose also resulted in the development of high avidity polyclonal serum, indicating affinity maturation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Both CpG and QuilA were found to be strong Th1 polarizing adjuvants, as indicated by the IgG2c skewed response, which has been suggested to be an important correlate of protective immunity against Q fever. 15,50,56 Further analysis of serological responses to Sol II revealed a dose-dependent correlation with an increasing IgG2c ratio. Increasing the number of doses or administering a higher dose also resulted in the development of high avidity polyclonal serum, indicating affinity maturation.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have indicated Th1 immune responses are an important correlate of protective immunity against Q fever. 15 , 50 , 51 For this reason, CpG was selected as the adjuvant of choice for all future Sol II immunizations.…”
Section: Resultsmentioning
confidence: 99%
“…High-dimensional cytometry, including mass cytometry and spectral flow cytometry, is a powerful technique to monitor immunity, identify cell subsets associated with diseases or potent responses to vaccines, and decipher the complex mechanisms of the immune response to vaccines (20)(21)(22)(23)(24)(25)(26)(27). However, the comparison and integration of different datasets generated at multiple sites and on different days is challenging, even when using the same technology.…”
Section: Comparing High Dimensional Cytometry Datasetsmentioning
confidence: 99%
“…These highly multiparametric methods require bioinformatic expertise, allowing unsupervised analysis [86], with the advantage of automatically defining cell subsets that might been not highlighted with conventional supervised analysis, in addition to getting rid of operatordriven analysis bias. This may lead to the identification of novel cell populations that could be associated with an effective vaccine response [87,88].…”
Section: Immune Cell Phenotypic and Functional Analysismentioning
confidence: 99%